Which Personality Traits Moderate the Relationship Between Religious Capital and Depressive Symptomology in a National Sample of African Americans?. (July 2017) - Clark, Eddie M.; Holt, Cheryl L.; Wang, Min Qi; Williams, Beverly R.; Schulz, Emily
The present study examined the relationship between religious capital and depressive symptoms and the moderating role of the Big Five personality constructs in a national sample of African American adults. Data were collected from a national probability sample of 803 African American men and women using a telephone survey including measures of the Big Five personality traits, religious capital, and depressive symptomology. Most interestingly, there was evidence for Personality × Religious Capital interactions on depressive symptomology. Higher religious capital was related to lower depressive symptomology among persons with low conscientiousness or low openness to experience. However, religious capital was less related to depressive symptoms among those with high conscientiousness or high openness. This study reinforces the importance of examining the moderating effects of personality and perceived religious capital in understanding mental health outcomes. This information can be of use to practitioners in designing culturally appropriate interventions, including the use of capital from faith-based organizations.